Model Matematika Pengaruh Gempabumi Terhadap Bangunan Bertingkat - Latifah Hanum; Muhammad Subhan (Journal of Mathematics UNP, 2020)
Abstract — Earthquakes have an impact on building damage. Buildings with low-rise floors are often found to be damaged more than multi-storey buildings. The aim of the research is to  investigate the movement of the building floor to see the structure response of building to the earthquake. Research on mathematical models of the effect of earthquakes on multi-storey buildings involves a system of differential equation which is solved by applying the eigenvalue method and eigenvector. The effect of coulomb damping is also incorporated in this study. The results of the study will show the history of displacement time, velocity, and acceleration of each building floor to earthquake loads and the relationship between natural frequency and earthquake time period. Keywords — Mathematical Modelling, Earthquake, Coulomb Damping.